HERITABILITY ESTIMATE AND GENETIC RESPONSE TO SELECTION FOR YEARLING WEIGHT IN BALI CATTLE - Warmadewi, D.A.; Oka, L.; Suyadnya, P.; Sudana, I.B. (E-Journal Of Animal Science Udayana University; Vol 3, No 1, Tahun 2014)
This study was carried out at Bali Cattle Breeding Centre ( BPTU Sapi Bali ) in Pulukan, Jembrana, Bali from March to November 2012. The aims of study were to estimate the heritability and genetic response to selection for yearling weight in Bali cattle. Records on 350 yearling weights of Bali cattle born from 2007 to 2011 at the Bali Cattle Breeding Centre were used in this study. The results showed that the average coefficient of variation for yearling weight of Bali cattle was 18.28%, the estimated heritability (h 2 ) was 0.42 ± 0.19, and the selection intensity was 0.92.  This value ??indicated that selection for this trait might improve the genetic quality of Bali cattle particularly in their liveweight at one year old.  Estimation of genetic response (Rg) obtained in this study was 9.02 kg.  The average generation interval in this population was 4.48 years.  Therefore, response per year (Ry) for yearling weight in this breed of cattle was 2.01 kg.  Based on this response per year, prediction for response in the year 2010 and 2011 were 6.03 kg and 12.06 kg respectively.  It was concluded that the heritability estimate of yearling weight in Bali cattle was categorized high and selection for this trait responded effectivelly
Keywords: Bali cattle, coefficient of variation, heritability, generation interval, selection intensity, genetic response